Pengaruh Leverage, Growth Opportunity, Ukuran Perusahaan dan Intensitas Modal terhadap Konservatisme Akuntansi - Suci Kurnia Putri; Wira Lestari; Riski Hernando (Universitas Negeri Padang, 2021)
The purpose of this study is to examine the effect of leverage, growth opportunity, firm size and capital intensity on accounting conservatism in the banking sector listed on the Indonesia Stock Exchange (IDX) both simultaneously and partially. The banking sector listed on the Indonesia Stock Exchange (IDX) was selected for the population in this study. The sample selection was carried out using purposive sampling technique and obtained 28 companies with a research period of four years of observation (2016-2019). Meanwhile, the data analysis in this study used multiple regression analysis methods using the SPSS version 22 for windows software application. The results of research conducted in this research indicate that the variable leverage, growth opportunity, firm size and capital intensity simultaneously affect accounting conservatism and firm size variables affect accounting conservatism partially. Meanwhile, other variables such as: leverage, growth opportunity, capital intensity show no effect on accounting conservatism partially. Keywords: Accounting Conservatism; Leverage; Growth Opportunity; Firm Size; Capital Intensity